2022
DOI: 10.1186/s41983-022-00578-3
|View full text |Cite
|
Sign up to set email alerts
|

Translating neuroimaging changes to neuro-endophenotypes of autistic spectrum disorder: a narrative review

Abstract: Background Autism-spectrum disorder is a neurodevelopmental disorder with heterogeneity in etiopathogenesis and clinical presentation. Neuroanatomical and neurophysiological abnormalities may represent neural endophenotypes for autism spectrum disorders which may help identify subgroups of patients seemingly similar in clinical presentation yet different in their pathophysiological underpinnings. Furthermore, a thorough understanding of the pathophysiology of disease can pave the way to effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 140 publications
(153 reference statements)
0
1
0
Order By: Relevance
“…ASD is a neurodevelopmental disorder characterized by severe and pervasive impairment in reciprocal socialization, qualitative impairment in communication, and repetitive or odd behavior. Recently, it has been determined that autism is a disorder of genetic [ 71 ] and neurological origin with defects in the coordinated functioning of various brain regions [ 72 , 73 ]. Many studies have reported a lower synchronization of the activation (or functional connectivity) between frontal and posterior brain regions in ASD subjects in a wide variety of tasks [ 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ], including language comprehension tasks [ 82 ].…”
Section: Introductionmentioning
confidence: 99%
“…ASD is a neurodevelopmental disorder characterized by severe and pervasive impairment in reciprocal socialization, qualitative impairment in communication, and repetitive or odd behavior. Recently, it has been determined that autism is a disorder of genetic [ 71 ] and neurological origin with defects in the coordinated functioning of various brain regions [ 72 , 73 ]. Many studies have reported a lower synchronization of the activation (or functional connectivity) between frontal and posterior brain regions in ASD subjects in a wide variety of tasks [ 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ], including language comprehension tasks [ 82 ].…”
Section: Introductionmentioning
confidence: 99%